Integrative Neuro-Endocrine Pathways in the Control of Reproduction in Lamprey: A Brief Review - Freamat, Mihael; Sower, Stacia A. (Frontiers in Endocrinology, 2013)
The gonadotropin-releasing hormone (GnRH) system is well known as the main regulator of reproductive physiology in vertebrates. It is also part of a network of brain structures and pathways that integrate information from the internal and external milieu and coordinate the adaptive behavioral and physiological responses to social and reproductive survival needs. In this paper we review the state of knowledge of the GnRH system in relation to the behavior, external, and internal factors that control reproduction in one of the oldest lineage of vertebrates, the lampreys.